Amendments 15 and 24 rights of citizens to vote/poll tax - Fabian, Rhonda; Baber, Jerry; Cambridge Educational (Monmouth Junction, N.J. : Cambridge Educational, 1998)
This program explores the fifteenth and twenty-fourth amendments: their orgins, real-world applications, history of interpretation in the nation's courts, and implications for the future. Combining computer graphics, original live-action video, historical artwork, and archival footage with narration and interviews, this program illustrates the importance of the amendments in the history of the United States
Title from cover
Adapted from Amendments to the Constitution : a brief legislative history
Executive producer, Edward T. Gardner ; camera, Mark Dombrow ; editors, Jonathan M. Danley, Ron Schindlinger ; writers, Aaron Myers, Jack Phelan, Rhonda Fabian
Narrator : Gene Shay
Keywords: United States; United States; Constitutional amendments -- United States; Poll tax -- United States; Suffrage -- United States